Clinical outcome in low socioeconomic patients with severe acute pancreatitis treated either with early nasogastric tube or total parenteral nutrition: a randomized controlled trial - Kumar, Anil; Paswan, Shiv S.; Kishor, Shiv; Bhandari, Vimal (International Surgery Journal, 2019)
Background: Early nasogastric feeding has shown beneficial effect in the low socioeconomic group of patient with severe acute pancreatitis (SAP). The current randomized controlled study was performed to assess the effect of early nasogastric feeding as compared to total parenteral nutrition (TPN). Methods: Fifty patients admitted with diagnosis of SAP were randomly allocated to receive nnteral feeding (EF) (at the rate of 25 ml/hour and was gradually increased up to 100 ml/hr) or TPN within 24 hours of hospital admission. The nutritional regimen was aimed to be iso-caloric between the two groups. Patient’s demographics, hospital stay, nutrition, total cost, complication, and mortality were observed for 1 month in follow up. Results: All fifty patients were completed the study. Patient demographics were similar in both groups. 38/50 belonged to low socioeconomic status in the study group (Twenty in EF and eighteen in TPN group). The complications were significantly lower in EF group (pancreatic infection (11 vs. 4, p=0.037), central venous catheter infection (EF=0 vs. TPN=8, p=0.002), multiorgan failure (EF=5, TPN=12, p=0.037). Early recovery in EF group was significant with the mean duration of hospital stay of 6.76 days as compared to 10.4 days in the TPN group. The mean expenditure in the EF group was 1268 as compared to 13688 Indian rupees in the TPN group. Conclusions: This study shows that early EF improves early recovery, lower complications and cost effective measure in SAP especially in low socioeconomic group of patients.